Development of Smart System for Renewable Energy Hybrid Power System Base on SCADA - . Suriadi; Soib Taib; Mohd Shawal Jadin; Azman Nordin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This paper presents the development of smart energy monitoring and control system for Renewable Energy Hybrid Power Generation System (REHPGS) using SCADA. REHPGS model consists of photovoltaic, wind and gen-set system. SCADA is used to monitor and control the operation of Hybrid Power System (HPS) in real time. This paper planned a concept of smart grid by VisconDua Remote Terminal Unit (RTU)-IO Module. The RTU is responsible to collect information from power HPS plant. SCADA Expert controller is introduced to automatically control renewable energy sources. The monitoring and control system of REHPGS operated in real time and can perform under various operating conditions. The HPS plant will be fully automated, which mean the power plant would rely on the SCADA system on all its operations. Results show that the proposed system has the capability to monitor and optimize the output power generation of REHPGS